Privacidade, liberdade de expressão e proteção dos dados pessoais: uma perspectiva brasileira com base na jurisprudência do Supremo Tribunal Federal - Pupo, Alvaro de Carvalho Pinto (2017)
This study analyzes the concept of intimacy, privacy, free speech and personal data under a brazilian perspective, as well as the protection for each of the itens mentioned. The study makes references to authorities, legislation and case law pertaining to each of the subjects. The study pursues the clarification of what each of these understands as privacy protection and personal data protection, and how these correlates. It also pursues to understand if these understandings are aligned and propose, in the end, some way of uniformization considering the legislative bill proposals being discussed in the Brazilian Congress